Pemberdayaan Optimalisasi Aset Wisata Melalui Kkn: Studi Kasus Di Desa Silurah - Taufiq, Ahmad; Nada, Alya Qothrun; Fathuddin, Ahmad Ubaedi; Munia, Yasmin Zahra (Dharmahita: Journal of Community Service and Development, 2025)
The service of real work college (KKN) students aims to help solve social, economic, and cultural problems in the village or community, as well as provide real experience to students in community service. in realizing the development of village assets aims to realize a village that can advance to become a Silurah tourist village, by helping to build marketing management to become a famous tourist. The service method used by the implementation team used descriptive qualitative through thorough observation during community service. Data collection was carried out by interviewing the village administration, pokdarwis as a community group formed consciously and voluntarily with the a im of developing, managing, and promoting tourism potential in their area, and karangtaruna. Furthermore, a survey was conducted in the planning stage to explore the tourism potential of the village. The implementation of the work program was carried out to address the challenges and potential development of Silurah Village as a result of infrastructure and accessibility development, increasing tourist attractiveness, strengthening the capacity of human resources (HR), developing creative economic production, promoting and digitizing tourism, strengthening partnerships and collaboration.